Domestic violence at the margins: readings on race, class, gender, and culture - Sokoloff, Natalie J. (Rutgers University Press)
Domestic violence : examining the intersections of race, class, and gender / Natalie J. Sokoloff and Ida Dupont -- Strengthening domestic violence theories / Michele Bograd -- Feminism versus multiculturalism / Leti Volpp -- A black feminist reflection on the antiviolence movement / Beth E. Richie -- Women's realities / Shamita Das Dasgupta -- Compounding the triple jeopardy / Valli Kalei Kanuha -- The intersectionality of domestic violence and welfare in the lives of poor women / Jyl Josephson -- Gender violence and the prison industrial complex -- Incite! critical resistance statement -- Violence in African American communities / Robert L. Hampton, Ricardo Carrillo, and Joan Kim -- Nashville / Neil Websdale -- Violence in ethnically diverse families / Carolyn M. West -- The importance of community in a feminist analysis of domestic violence among American Indians / Sherry L. Hamby -- Rethinking battered woman syndrome / Sharon Angella Allard -- Recent development --domestic violence in the Jewish community / Beverly Horsburgh -- "I've slept in clothes long enough" / Lois Weis, Michelle Fine, Amira Proweller, Corrine Bertram, and Julia Marusza -- Fighting back / Margaret Abraham -- Puerto Rican battered women redefining gender, sexuality, culture, violence, and resistance / Michelle Fine, Rosemarie A. Roberts, and Lois Weis -- The cultural context model / Rhea V. Almeida and Judith Lockard -- Battering, forgiveness, and redemption / Brenda V. Smith -- Sustaining an ethic of resistance against domestic violence in black faith-based communities / Traci C. West -- Navigating the anti-immigrant wave / Lisa Sun-Hee Park -- Shifting power for battered women / Donna Coker -- Reducing woman battering / Neil Websdale and Byron R. Johnson -- Looking to the future / Andrea Smith